Investigating materiality through art-based research / Choy Chun Wei - Choy , Chun Wei (2016)
This research paper investigates art materiality through the emerging Art-Based Research methodology (Eisner, E.W.2002; Sullivan, G.2010; Chilton, G. and Leavy, P. 2014; Daichendt, G.J.2012). As an artist-researcher, I intend to describe, examine, and finally innovate the artistic methods and functions (of materiality process) in my artworks produced within 2001 and 2011. Though the lens of Art-Based Research, my own visual art practice will be formulated into two processes of interpretive research practices (Sullivan, G.2010) - that is “the Reflective” and “the Generative” research domains. As for the former, I will conduct the theorization process of past exhibited artworks (Sullivan, G.2010) selected from the time-frame of ten years – that is from the year of 2001 till 2011. For this purpose, I will be employing Eisner, E.W. (2002) Criticism method as a framework to “interpret” into the collage methods and changes within the materiality process over the selected past artworks. The findings of reflective research practice showed that the malleability of the materiality process were determined and impacted by different stages of life-experiences and thought processes. The findings of Reflective case study six were then taken as “theme”/”trigger point” to be explored as a new artwork in Generative Practice ( Five weeks study). The new artwork developed from the Generative practice is a greater clarity and the delimiting of choices led to a more purposeful materiality presence and visual impact. The research also showed that through Art-Based Research practices (Reflective and Generative), I have attained a deeper understanding of situated collage methods, and understanding the vital role collages methods in resisting the mass media and over consumption perpetuated by the imperative nature of consumer culture and environment.